For the Good of Russia - V. P. Gridnev (Управленческое консультирование, 2022)
The relevance of the topic is due to the fact that in modern conditions the relevance of the topic is due to the fact that in modern conditions the role and importance of patriotic education of the younger generation is increasing. Youth is the future of the country and is the barometer of society. The processes that are taking place in the country and around the world are confirmation that young people want to actively participate in the political life of the country, increasing its rating in the international arena. And in this case, history presents an example of the service of faith and truth to the Russian state by Empress Catherine the Great, who set the main goal to revive the power of the Russian Empire and improve the life of the country’s population. Ekaterina, upon taking office, was engaged in reforming the system of public administration, carrying out customs and monetary reforms, increasing the territory of the Russian state, increasing the population of the country, actively counteracting bribery, educating the younger generation, preparing “a new breed or new fathers and mothers, morally perfect”.